2022
DOI: 10.3390/ma15228123
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Progressive Damage and Failure of Single-Lap Thin-Ply-Laminated Composite-Bolted Joint Using LaRC Failure Criterion

Abstract: Thin-ply composite failure modes also significantly differ from conventional ply composite failure modes, with the final failure mechanism switching from irregular progressive failure to direct fracture characterized by a uniform fracture with the reduction of the ply thickness. When open holes and bolt joints are involved, thin-ply-laminated composites exhibit more complex stress states, damage evolution, and failure modes. Compared to the experimental study of thin-ply-laminated composite-bolted joints, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Existing studies (Bouchahdane et al ., 2022; Wei et al ., 2020; Wang et al ., 2022) have shown that the fatigue damage propagation law of damage-containing laminates and open-hole laminates is similar to the strength failure mode. With a combination of calculation and simulation, the equivalent relationship between the residual strength of CAEI and the residual strength of the open-hole compression laminate is established in this paper.…”
Section: Numerical Simulation Of Equivalent Modelmentioning
confidence: 99%
“…Existing studies (Bouchahdane et al ., 2022; Wei et al ., 2020; Wang et al ., 2022) have shown that the fatigue damage propagation law of damage-containing laminates and open-hole laminates is similar to the strength failure mode. With a combination of calculation and simulation, the equivalent relationship between the residual strength of CAEI and the residual strength of the open-hole compression laminate is established in this paper.…”
Section: Numerical Simulation Of Equivalent Modelmentioning
confidence: 99%